Perancangan Aplikasi Pembangkit Identitas File Dokumen Menerapkan Algoritma Fungsi HASH MD2 - Ndruru, Suriani (Jurnal Kajian Ilmiah Teknologi Informasi dan Komputer, 2024)
Currently in the digital world era. However, now many industries have switched to digital technology such as photos, videos, music and so on. Of course, this change brings many benefits to us in terms of data access speed. Another advantage of computer technology is in terms of copying and generating digital file identities where the results will have the same identity value. So if you want to distinguish one document file from another, it will be very difficult because you have to check the entire contents of the document file. In cryptography there is a hash function which is a one-way function that can generate the identity of a file. Where if the document file has the same contents, it will produce the same hash value. This can be used to identify the same document file. In the hash function there is an MD2 method or the design of a document file identity generator application applies the MD2 hash function algorithm which is one of the hashing algorithms that is often used to encrypt data with a width of 20 bytes or 160 bits. By applying this algorithm to the identity document application, the results of the document file search are grouped based on the same hash value and users can easily and quickly delete document files with the same identity without having to open and read the contents of the file.